Isolation and Molecular Detection of Bacteria from Frequently Touched Objects of Various Public Places at Sadar Upazila of Mymensingh District (Journal of Science and Technology Research, 2024)
The current research was conducted to investigate the magnitude of bacterial contamination in public buses, different wards of hospitals, and public toilets of bus stations and hospitals in Sadar Upazila, Mymensingh, Bangladesh. A total of 90 swab samples were collected aseptically from the most frequently touched surfaces of the sample area. Identification of the isolated bacteria was done by staining and biochemical tests, followed by molecular detection by PCR using genus or speciesspecific primers. Isolated organisms were then subjected to an antibiotic sensitivity test using disk diffusion techniques using 13 commonly available antibiotics. Among the samples, 76.67% (n=69/90) were positive for E. coli, 80% (n=72/90) were positive for Klebsiella spp., and 68% (n=61/90) were positive for Staphylococcus spp. Positive tetA and stx-1 genes were found in 40 and 19 E. coli isolates, respectively. 23 positive mecA genes, or MRSA, were found in Staphylococcus aureus isolates that pose a threat to public health. Toilets of the bus stations were the most contaminated place by the selected bacteria, with the prevalence of E. coli,Klebsiella spp., and Staphylococcus aureus being 81.48% (n=22/27), 77.78% (n=21/27), and 81.48% (n=22/27), respectively. In an antibiogram study, E. coli isolates showed 100% resistance against amoxicillin, azithromycin, tetracycline, and co-trimoxazole. Klebsiella spp. was revealed to be 100% resistant to amoxicillin, followed by colistin sulfate (60%). Staphylococcus aureus isolates were 100% resistant to methicillin, cefoxitin, and cefixime. The findings can be used to raise public awareness about the possible threat, hence preventing the spread of infectious disease in public places.J. of Sci. and Tech. Res. 6(1): 125-137, 2024